Après le Défi Américain: la Structure Multidivisionelle dans l’Europe Post-McKinsey - Whittington, R; Mayer, M (2003)
This paper examines the trajectory of the multidivisional structure in Europe during the 1980s and 1990s - i.e. after "the American challenge". As an American import, the multinational structure's continued success is doubted by both "national institutionalists", stressing the idiosyncracy of national management models, and "international institutionalists", stressing the transitory influence of American mangement models. The paper finds that in fact the American multinational has become an enduring model for big business in France, Germany and Britain, even if adoption has been slower than originally predicted by its proponents. The paper concludes by discussing the implications for institutional theory and the role of consulting firms and similar in the international transfer of mangement models.